Claiming Justice: An Analysis of Child Sexual Abuse Complainants’ Justice Goals Reported during Investigative Interviews - Robyn L. Holder; Dirkje Gerryts; Francisco Garcia; Martine Powell (Laws, 2023)
Investigative interviewing of children who report sexual victimisation focuses on helping children tell in their own words what happened. Children may say other things important to them such as their justice goals. We conducted the first research into this possibility in an exploratory analysis of 300 transcripts of actual interviews with child complainants aged 3 to 15 years. Building on an earlier study involving adults, we explored what goals children may articulate, when in the interview process their goals are relayed and in response to which interviewer prompts. Our analysis revealed that most children did articulate one or more justice goals during these interviews, especially their desire for acknowledgement of the victimisation and its wrongfulness. Children articulated their justice goals spontaneously and largely without any direct prompting by the police officer. These findings suggest that there is more that institutions [and researchers] can learn from carefully listening to children and understanding them as agents claiming justice.